Coming 2 America [videorecording (Blu-Ray)] - Barris, Kenya, 1974-; Blaustein, Barry W.; Sheffield, David, 1948-; Kanew, Justin, 1979-; Murphy, Eddie, 1961-; Hall, Arsenio; Fowler, Jermaine; Jones, Leslie, 1967-; Morgan, Tracy, 1968-; Layne, KiKi; Headley, Shari, 1964-; Snipes, Wesley; et al. (Paramount Pictures, 2022)
Akeem and Semmi are back! Set in the lush and royal country of Zamunda, newly-crowned King Akeem and his trusted confidante Semmi embark on an all-new hilarious adventure that has them traversing the globe from their great African nation to the borough of Queens, New York, where it all began.